Wittgenstein's Tractatus deranged : a metaphilosophical story - Silva, João Esteves da (2019)
Taking off from some the more recent discussions regarding the puzzling character of Ludwig Wittgenstein’s Tractatus Logico-Philosophicus, this dissertation aims at four main points, mostly negative ones, all closely related when considered from a Wittgensteinian angle: an exegetical, a metaphilosophical, a linguistic, and an ethical point. [1] Serving as a background illuminating the remaining three, the exegetical point is concerned with the particular modes of philosophical criticism Wittgenstein’s works ask for, favouring the idea that it is impossible to expound them as something finished, and so than even the Tractatus shall prove more profitable when taken as a collection of remarks, not as a system. [2] Arguably as pivotal, the metaphilosophical point expounds a non-metaphysical view of philosophy, aware of its own mutable, given its contiguity with all our other activities, and practical character: philosophy, we hold, following Wittgenstein, is the art of (dis)solving intellectual puzzles, a contribution to understanding, not to knowledge. [3] The linguistic point is somewhat made manifest by the former: the ways of doing philosophy here adopted, relying as much on hinting (often through the deliberate employment of figurative modes of expression or even nonsense) as on argument, end up indirectly drawing attention to the untenability of the idea that language might be a somewhat self-sufficient and clearly defined structure, asking for definitive explanations of its workings. [4] As for the ethical point, a complaint against prevailing contemporary approaches to ethics and aesthetics, and alongside the more or less subtle hints already provided by the other three, silence has been the chosen method to intimate it. Though mostly focused on the Tractatus, the present dissertation, tendentially favourable to the spirit of the “New Wittgenstein”, is meant to serve as a kind of window, even if a tiny one, to the Philosophical Investigations as well.